Pedagogical Conditions Related to the Formation of Professional Value Orientations of Law Students - Vasylchenko, O.; Vertegel, V.; Khrebtova, V.; Murzina, O. A.; Мурзіна, Олена Анатоліївна (My University, 2020)
The article aims to examine the issue of the law students’ professional values and their formation in the system of higher education particularly in the Ukrainian context. The authors analyze the term “value orientations” as an important component of the structure of the individual and define law students’ professional value orientations and consider professional values’ formation of future lawyers as their personal development in real processes of their education at university. Professional self-identification, selfrealization, and self-organization are defined as essential value orientations for future specialists.
Keywords: pedagogical condition; professional value orientations; professional self-identification; law students; value-forming component; academic material of value oriented character